THE ROLE OF BUSINESS RISK AS AN INTERVENING VARIABLE ON FACTORS AFFECTING COMPANY VALUE - Natsir, Khairina; Bangun, Nurainun; Ngadiman , Ngadiman; Chiandra, Febbyorent (Graduate Program of Universitas Tarumanagara, 2024)
This study heading to examine the effect of “dividend policy, investment decisions and funding decisions on firm value by applying business risk as an intervening variable. The population is companies in the consumer goods industry sector that are listed on the IDX in 2016-2022. Samples were selected by purposive sampling. Research data were obtained from the official website of the Indonesia Stock Exchange www.idx.co.id and the official website of the company under study. Data analysis was performed using multiple regression methods. The selection of the regression model was carried out through the Chow test, Hausman test, and Lagrange Multiplier test. The classic assumption test includes a multicollinearity test. Hypothesis testing includes the t-test and the coefficient of determination test. To analyze the effect of mediation is done through the Sobel test, Goodman test, and Aroian test. The results of the study show that dividend policy, investment decisions, funding decisions, and business risks affect firm values. The mediation test using the Sobel, Aroian and Goodman method shows that business risk is able to mediate dividend policy on firm value, business risk variables do not mediate funding decisions on firm value. Meanwhile for the mediation test between investment decisions and firm value, different results were obtained between the three test methods carried out, where Sobel and Aroian showed that investment decisions on firm value were not mediated by business risk, while the Goodman Test showed that there is a significant influence of business risk variables as mediating variables.”